Assessment of muscle mass relative to fat mass and associations with physical functioning in rheumatoid arthritis. (28th February 2017) - Baker, Joshua F.; Giles, Jon T.; Weber, David; Leonard, Mary B.; Zemel, Babette S.; Long, Jin; Ibrahim, Said; Katz, Patricia P.
Abstract: Objectives. To determine whether a novel measure of appendicular lean mass relative to fat mass is associated with physical functioning in RA. Methods. In a cross-sectional design, three independent RA cohorts were retrospectively analysed. Whole-body DXA measures of appendicular lean mass index (ALMI, kg/m 2 ) and fat mass index (FMI, kg/m 2 ) were converted to age, sex and race-specific Z-scores using published National Health and Nutrition Examination Survey reference ranges. Adiposity-adjusted ALMI Z-scores (ALMIFMI ) were determined using a published method to adjust for normal associations between ALMI and FMI Z-scores. Associations between ALMI Z-scores, ALMIFMI Z-scores and physical functioning were assessed after adjusting for age, sex and study. Functional outcomes assessed included the HAQ, Valued Life Activities assessment and Short Physical Performance Battery. Low lean for age was defined as a Z-score of −1 or less. Results. Our sample consisted of 442 patients with RA. The combined cohort had a mean ALMI Z-score of − 0.51 (1.08) and a mean ALMIFMI Z-score of − 0.58 (1.53), suggesting muscle mass deficits compared with a nationally representative sample. Greater ALMIFMI Z-scores demonstrated stronger associations with better functional outcomes compared with ALMI Z-scores. Associations were not attenuated with adjustment for systemic inflammation or pain. The FMI Z-score was independently associated with physical functioning, with a stronger association seen among patients with greater FMI Z-score. Adiposity-adjusted definitions of low lean mass more clearly identified those with functional impairment. Conclusion. Estimates of appendicular lean mass that are adjusted for adiposity demonstrate stronger positive associations with functional outcomes compared with unadjusted estimates.